Case Report: 68Ga-FAPI PET/CT, a more advantageous detection mean of gastric, peritoneal, and ovarian metastases from breast cancer - Li, Tianyue; Jiang, Xiaojing; Zhang, Zhaoqi; Chen, Xiaolin; Wang, Jianfang; Zhao, Xinming; Zhang, Jingmian (Frontiers in Oncology, 2022)
Breast cancer is the most common malignant tumor in adult women. Its common metastatic sites are lymph nodes, bones, lungs, liver and brain. It is so rare for a patient with breast cancer to have metastases of gastrointestinal tract, peritoneum and ovary at the same time that the clinical reporting rate is low. We present a case of a 61-year-old woman who underwent right mastectomy and chemoradiotherapy three years ago because of mixed invasive ductal-lobular breast cancer. This time, she came to the hospital due to the symptom of stomach discomfort for two weeks. The gastroscopy biopsy result was gastric metastasis from breast cancer. Then 18F-FDG and 68Ga-FAPI PET/CT imaging were performed for further diagnosis, 68Ga-FAPI PET/CT demonstrated significantly elevated FAPI activity in the thickened gastric wall, peritoneum and bilateral adnexal areas, which was superior to that of 18F-FDG. Finally, biopsy of suspicious lesions was taken for pathological and histochemical examination which confirmed that, besides the gastric metastasis, the peritoneum and bilateral ovaries were all consistent with metastatic breast cancer.